2010
DOI: 10.1111/igc.0b013e3181d7ce94
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Disease Relapse in Surgical Stage I Endometrioid Adenocarcinoma of the Uterus After Adjuvant Vaginal Vault Brachytherapy

Abstract: This treatment has excellent survival rates with acceptable morbidity, and recurrence is mostly distant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…In addition, it is commonly expected that pelvic EBRT would contribute more to postoperative LEL than vaginal brachytherapy. Indeed, the incidence of lymphedema after adjuvant vaginal brachytherapy ranges from 3.7% to 11.1% [23,25], which is relatively low compared to 25.5% to 71.4% after adjuvant pelvic EBRT [4,10], except one study that reported lower incidence of LEL after pelvic EBRT than after vaginal brachytherapy [14]. However, to our knowledge, this is the first study to perform direct comparison of the risk of LEL following pelvic EBRT and vaginal brachytherapy and to show that pelvic EBRT is associated with higher risk of postoperative LEL.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is commonly expected that pelvic EBRT would contribute more to postoperative LEL than vaginal brachytherapy. Indeed, the incidence of lymphedema after adjuvant vaginal brachytherapy ranges from 3.7% to 11.1% [23,25], which is relatively low compared to 25.5% to 71.4% after adjuvant pelvic EBRT [4,10], except one study that reported lower incidence of LEL after pelvic EBRT than after vaginal brachytherapy [14]. However, to our knowledge, this is the first study to perform direct comparison of the risk of LEL following pelvic EBRT and vaginal brachytherapy and to show that pelvic EBRT is associated with higher risk of postoperative LEL.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the overall (25.5%) and distant (17%) recurrence rates in patients with LVSI-positive EEC next to 2 to 3 risk factors who received adjuvant radiotherapy were much higher than those of patients with comparable risk factors and treatment who were not selected based on the presence of LVSI, as assessed by the primary pathologist. 5,12,14 In our study, all patients who died of endometrial cancer had recurrent disease, and all but one had a distant component. A group of patients who did exceptionally well were those with grade 1 EEC.…”
Section: Discussionmentioning
confidence: 57%
“…12,13 By contrast, other studies showed that VBT is equally effective to EBRT in patients with endometrial cancer and LVSI. 7,14 In the presence of LVSI, both lymphadenectomy and systemic treatment have been proposed. 3,15,16 So far, the implications of LVSI in patients with stage I EEC on either primary or adjuvant treatment have not been well established.…”
mentioning
confidence: 99%
“…41,53 Other studies comparing EBRT with HDIVRT have reported excellent recurrence-free and overall survival rates. 54 These findings suggest that early stage endometrial cancer patients can avoid the high morbidity associated with EBRT by receiving HDIVRT. 52 The PORTEC-2 Trial did confirm, however, that HDIVRT patients experience vaginal toxicities (dryness, tightening, and shortened vagina) and dyspareunia.…”
Section: Cancer Treatment and Sexualitymentioning
confidence: 81%